Determining biological effects of functional amino acid supplementation in low crude protein diet on growth performance of layer chicken - Mohan, Tenesa; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Saad, Wan Zuhainis; Mohamad, Rosfarizan; Abdul Rahim, Raha (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
This investigation sought to determine the biological effects of functional amino acids on the growth performance of layer chickens. A total of 144 Hisex Brown hens were allocated into 4 groups that were each fed low crude protein diet from 16 to 32 weeks of age. Diets contained 17.5% CP (control group), 17.5% CP, 17% CP and 16.5% CP and were supplemented with limiting AA (methionine, lysine and threonine). Weekly feed intake, egg weight, hen-day egg production and feed conversion ratio (FCR) were collected. There was no significant difference (P>0.05) among the treatment groups on overall feed intake, egg weight and egg mass. Significant higher (P<0.05) overall hen-day egg production was observed in all treatment groups compared with the control. Overall, 17.5% CP diets resulted in better egg production than other treatments.